Pengaruh Digital Marketing Terhadap Perilaku Konsumen Pada Masa Pandemi Covid-19 - Nur, Salsa Zakiyah (PT Literasi Nusantara Publisher, 2024)
The increasingly rapid development of technology has led to increased globalization which has had an influence on all areas of human life, this has caused cultural changes so that activities are carried out with a lifestyle that cannot be separated from electronic devices. This situation requires companies and business owners to change their marketing strategies to become completely digital. Companies and business owners must do this through digital marketing strategies in order to maintain and be able to compete in the digital era. Moreover, the occurrence of the Covid-19 Pandemic in 2020 further strengthened and intensified people's attention to online media due to the implementation of government policies related to social authorities to prevent the transmission of the virus in society. This policy caused a decline in economic activity, resulting in an economic crisis that required business actors to maintain their business through digital marketing. This research uses multiple linear regression (MLR) analysis to see the influence of digital marketing on consumer behavior before and after the Covid-19 pandemic. The research results show that digital marketing influences consumer behavior before and after the Covid-19 pandemic. Based on this, it is concluded that digital marketing can influence consumer behavior in purchasing goods or services before and after the Covid-19 pandemic.